Factors perceived to contribute to the success of some selected school libraries - Sison, Gliceria C. (Institute of Library Science, University of the Philippines Diliman, 1989)
The study aims to determine the following: 1) factors that are perceived to contribute to the effectiveness of school libraries; 2) the importance of these factors to the effectiveness of four selected grade school libraries in Metro Manila namely Ateneo, San Beda, Assumption, and St. Scholastica; and 3) whether school administrators, teachers and librarians differ in their perceptions of these factors in relation to their libraries.